Sudanese and Somali Refugees in Canada: Social Support Needs and Preferences. (1st August 2013) - Makwarimba, Edward; Stewart, Miriam; Simich, Laura; Makumbe, Knox; Shizha, Edward; Anderson, Sharon
Abstract: The aim of the study was to identify the unique support needs and preferences of African refugees in Canada. In‐depth interviews were conducted with Sudanese and Somali refugees (n=68) living in two cities in central and western Canada. Refugees were interviewed individually to identify their support needs, current sources of support, available support programmes, barriers to access to support resources, and preferred support interventions. These refugees reported major support needs, depleted social networks, and barriers to accessing services and supports. They identified distinct preferences for support from peers from the same country of origin and professionals. Participants wanted group‐level support supplemented by one‐to‐one support. Transportation, child care, meals, and peers matched by language and gender were recommended to enhance accessibility to support programmes. These findings can inform the design of support intervention research and enhance the relevance and supportiveness of services and programmes for recent refugees.